The subsea electrical analysis based on support vector machine - Sun, Ming Ming. (2013)
This Industrial Sponsored Project (ISP), which is describes in this report, is collaborated between the author` s sponsored company, FMC Technologies Singapore and NTU School of Electrical and Electronics Engineering. It aims to develop a prediction tool for the subsea electrical analysis to improve the engineering work efficiency in the industry.